2022
DOI: 10.3390/ijms232415477
|View full text |Cite
|
Sign up to set email alerts
|

Circ-ERC2 Is Involved in Melatonin Synthesis by Regulating the miR-125a-5p/MAT2A Axis

Abstract: The circadian rhythm of melatonin secretion in the pineal gland is highly conserved in vertebrates. Melatonin levels are always elevated at night. Acetylserotonin O-methyltransferase (ASMT) is the last enzyme in the regulation of melatonin biosynthesis (N-acetyl-5-hydroxytryptamine-melatonin). S-adenosylmethionine (SAM) is an important methyl donor in mammals and can be used as a substrate for the synthesis of melatonin. Methionine adenosyltransferase (MAT) catalyzes the synthesis of SAM from methionine and AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…These observations indicate the potential of circRNAs in the regulation of circadian rhythm. Studies have demonstrated that circRNAs influence melatonin metabolism and circadian rhythm by sponging miRNAs in the pineal gland [20,56]. Cir-cRNA Cdr1as strongly regulates light entrainment during a 12:12 h light/dark cycle in the SCN tissue [21].…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicate the potential of circRNAs in the regulation of circadian rhythm. Studies have demonstrated that circRNAs influence melatonin metabolism and circadian rhythm by sponging miRNAs in the pineal gland [20,56]. Cir-cRNA Cdr1as strongly regulates light entrainment during a 12:12 h light/dark cycle in the SCN tissue [21].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin or melatonin receptor 1A has been widely reported to improve PCOS by modulating AR and key metabolic enzymes [101]. An in vitro study showed that circ-ERC2 regulates rhythmic melatonin production in rat pineal glands via the miR-125a-5p/MAT2a axis [102]. In addition, animal experiments have shown that continuous light exposure leads to altered circRNA expression profiles in rat ovaries.…”
Section: Circular Rnas and Circadian Rhythmmentioning
confidence: 99%